Crescimento agrícola, eficiência técnica e sustentabilidade ambiental - Felipe Pinto da Silva; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The objective of the present study is to estimate the factors that influencing global agricultural production, as well as to assess the technical efficiency of countries, taking account the context of climate change. The problem is: are countries that seek productive solutions to increase productivity and competitiveness the most efficient in a sustainable production logic? It is believed that the countries that increased the most production were those that intensified the emission of GHG (Greenhouse Gases), which leads to associate the false interpretation that growing countries pollute more. The hypothesis to be tested, therefore, is: the countries that grew the most (or increased production) were those that used the most technology that sequesters carbon, increasing its technical efficiency. To do this, a Stochastic Frontier model was used, based on the 1992-2014 data from 118 countries, available from the US Department of Agriculture (USDA), the World Bank and the Food Agriculture Organization (FAO). The study show that sustainable solutions in agricultural production, which increase the capacity of CO2 capture by soil, imply an increase in productive efficiency and that these measures are not fully disseminated worldwide, only in countries listed as more technically efficient.
Keywords: Q1; D24; Q54; 330; agriculture; production; climate change